Ant Colony Optimization Approach To Communications Network Design - Bau, Yoon Teck (2007)
Ant Colony Optimization (ACO) is a metaheuristic approach for solving hard combinatorial optimization problems. The pheromone trails in ACO serve as distributed, numerical information, which the ants use to probabilistically construct solutions to the problem being solved, and which the ants adapt during the algorithm's execution to reflect their search experience.